2015
DOI: 10.1016/j.aju.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Modular training for percutaneous nephrolithotripsy: The safe way to go

Abstract: Objectives should be describe a modular training scheme (MTS) which aims to provide training in percutaneous nephrolithotripsy (PCNL) and ensure the safety of the patients.Subjects and methodsTwo trainees with no experience in PCNL attended the MTS under the supervision of an experienced mentor. The MTS included five modules, comprising an initial animal laboratory course (using pigs), to acquire basic skills (Module 1), and Modules 2–5 included making the puncture, tract dilatation, single-stone and large-sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…[516171822] Moreover, in our study, most major complication events happened when higher grades of calculus complexity were tackled early in the learning curve (especially during first fifty cases) even though expert help was always available. Furthermore, we found that for both traditional and stepwise training groups the skill of the surgeon continued to grow, and complete clearance with no major complications was achieved in all cases of GSS 1 and 2 grade calculi which were operated beyond thirty and sixty case mark respectively.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…[516171822] Moreover, in our study, most major complication events happened when higher grades of calculus complexity were tackled early in the learning curve (especially during first fifty cases) even though expert help was always available. Furthermore, we found that for both traditional and stepwise training groups the skill of the surgeon continued to grow, and complete clearance with no major complications was achieved in all cases of GSS 1 and 2 grade calculi which were operated beyond thirty and sixty case mark respectively.…”
Section: Discussionmentioning
confidence: 88%
“…[5161718] A common theme observed was that surgical competence could be achieved at around sixty patients, whereas excellence is achieved after slightly more than 100 cases. Use of ultrasound guidance suggested no different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26] Only one study reported the use of anesthetized live pigs as module 1 of the Modular Training Scheme, which included renal puncture, tract dilatation using the Amplatz dilators, and orientation with the nephroscope in a live pig. 27 The PERC MentorÔ (Simbionix, Cleveland, OH) was the only VR simulator that has been validated for training and assessment of PCA skills. 12,13,[28][29][30][31] However, none of these studies assessed the educational impact of PCA simulators in terms of transferring PCA skills from the benchtop to the OR.…”
Section: Resultsmentioning
confidence: 99%
“…Earp [14] used porcine kidney encased in a foam layer. Kallidonis et al [15] and Mishra et al [16] studied the live anaesthetised pig as a model for PCNL training.…”
Section: Discussionmentioning
confidence: 99%